Pengembangan Sistem Informasi Pelayanan Pasien berbasis Web (Studi Kasus: Balai Pemasangan Gigi Setia Kawan) - Fathin Al Ghifari; Dian Eka Ratnawati; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Setia Kawan is a place that serves the manufacture and installation of dentures. The service flow starts from registration, calling, consulting, measuring, manufacturing, installing and paying. Setia Kawan has a problem, namely the recording of queue data and receipts is still done manually. This causes queues to pile up, as employees need to handle 2 jobs. Another problem is that when a patient wants to make a warranty claim, employees need time to make sure the receipt is genuine and valid by looking for data in the queue archive on that date. Because of this problem, Setia Kawan received criticism that the services provided were very long. Based on that problem, the researcher created a patient service information system which on the admin side has features to manage patient data, queues, bookings and payments. The information system on the Patient side has features for booking queues, changing schedules and canceling bookings. The development of this system uses the waterfall model because all requirements have been defined at the requirements analysis stage which produces 2 actors, 11 functional requirements and 1 non-functional. The implementation phase produces 12 interface pages on the Admin side and 4 on the Patient side. Based on the results of functional testing, both sides get a success value of 100%. The results of the usability test using the usability scale (SUS) system get 68 points for the admin frontend and 75 for the patient frontend. SUS for the admin frontend is in the OK and marginal categories, while the patient frontend is in the Good and Acceptable category.